Islamic Education Models: A Bibliometric Analysis of Challenges and Prospects - Mariam Elbanna; Muthoifin (Walidem Institute and Publishing (WIP), 2025)
Objective: This research aims to explore the dynamics of Islamic education through a bibliometric analysis, focusing on its challenges and prospects in the modern context. The study utilizes the VOSviewer software to systematically analyze 1,377 publications on Islamic education from 2015 to 2024, retrieved from the Scopus database. Theoretical framework: The theoretical framework is grounded in the interplay between traditional Islamic principles and modern educational paradigms, emphasizing the need for a balanced approach to preserving Islamic traditions while adapting to contemporary demands. Literature Review: The literature review identifies key themes in Islamic education research, such as traditional teaching methods, curriculum development, and the integration of technology. Additionally, emerging topics like inclusive education, the use of digital tools, and sustainability are highlighted as critical areas of focus for future development. Methods: The research employs a bibliometric analysis method, mapping co-authorship, co-citation, and keyword networks to identify dominant research trends, influential authors, and geographical patterns in the field. This approach enables a comprehensive understanding of the research landscape and its evolution over time. Results: The findings reveal that Islamic education faces a dual challenge: maintaining its spiritual and cultural essence while embracing innovation and globalization. Key insights include the increasing importance of digital tools in enhancing access and inclusivity, the need for curriculum reforms that incorporate skill-based learning, and the growing attention to sustainability in Islamic education. Despite progress, significant gaps remain in teacher training, policy implementation, and resource allocation, which require immediate attention. Implications: The implications of this study are multifaceted. For researchers, it offers a roadmap for addressing underexplored areas, such as the intersection of Islamic education and sustainable development. For practitioners, it provides actionable insights into improving educational practices and policies. Policymakers can leverage the findings to design initiatives that align Islamic education with the demands of the modern world while preserving its foundational values. Novelty: The novelty of this research lies in its comprehensive bibliometric approach, which systematically identifies gaps and opportunities in Islamic education, offering a forward-looking perspective that bridges tradition and modernity.